Analisis Strategi Bisnis Pada PT. Retrans Energi Perkasa dalam Meningkatkan Penjualan - Annisa, Resti (Bedelau: Journal of Education and Learning, 2022)
The purpose of this research is to find out what business strategies are suitable to be implemented at PT RETRANS ENERGI PERKASA. This descriptive research uses qualitative and quantitative analysis methods. Data processing uses SWOT matrix analysis, IE matrix, and Grand Strategy matrix. Through the QSPM matrix, results are obtained which show that a suitable strategy for use by the company is a market penetration strategy, where by implementing this strategy it is hoped that the company will be able to increase sales value, product quality and employee performance. Two other alternative strategies, namely product development and market development, are at the bottom of the list. For the company itself, it is hoped that it can apply this strategy to the planning system in order to prove the strategy that has been prepared.